Green walls and health: An umbrella review - Marcel Cardinali; Alvaro Balderrama; Daniel Arztmann; Uta Pottgiesser (Nature-Based Solutions, 2023)
Current societal challenges like climate change led to a general agreement that our cities need to become greener and our lifestyles more sustainable. This transformation of our daily living environments can also impact the prevalence of non-communicable diseases as a global disease burden of our time. These positive impacts of horizontal green spaces on human health are widely recognized. However, it is still unclear whether the same is true for green walls, as a promising nature-based solution for dense urban spaces which is increasingly applied. To date, the available research on green walls has not been systematically synthesized along the potential impact pathways of reducing environmental stressors (Mitigation), restoring capacities (Restoration), and promoting healthier behavior (Instoration). We conducted a systematic review of 30 reviews to synthesize available evidence on all three pathways and direct health outcomes, following the established strategies of PICOS and PRISMA. We assessed the review quality through AMSTAR. We found strong consistent evidence that green walls can mitigate urban heat island effects (daylight surface temperature: -0.3 °C to -31.9°, daylight air temperature: -0 °C to -8.7 °C), air pollution (PM2.5: -25% to -99%, PM10: -23% to -60%), and noise pollution (sound pressure level: -1dBA to -5dBA). We found some evidence for disaster risk reduction and restoration effects. There were no reviews on the instoration pathway or direct health outcomes. The underlying reviews rated low according to the AMSTAR checklist, which might limit our findings. We recognize a generally young research field and conclude that more in-field studies are needed in all pathways to better understand the relationship between green walls and health.